The Influence of Service Quality and Retail Innovation on Customer Satisfaction at Lequita Furniture - sukma, gio elang; Sahara, Sahara; Kustandi, Tedi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This research aims to examine the influence of service quality and retail innovation on customer satisfaction. The study is important as it provides empirical evidence on how service and innovation contribute to customer perceptions and loyalty in the retail sector. The expected outcome is to identify the extent to which these variables determine customer satisfaction. Methodology: The study applied a quantitative approach using multiple linear regression analysis. Data were collected through a structured questionnaire distributed to customers, and analyzed using statistical techniques including the t-test, F-test, and coefficient of determination (RÂ²). Â Results: The findings show that both service quality and retail innovation significantly affect customer satisfaction. The F-test results indicate a simultaneous positive and significant influence, while the t-test demonstrates that each variable individually contributes to customer satisfaction. The coefficient of determination reveals that service quality and retail innovation account for 62.8% of the variance in customer satisfaction. Findings: The research highlights that enhancing service quality and adopting innovative retail practices are key strategies for improving customer satisfaction. Novelty: Unlike prior studies, this research combines service quality and retail innovation as predictors of customer satisfaction in a single model. Originality: The study offers a unique contribution by empirically validating the joint effect of these two variables in the retail sector. Conclusion: Service quality and retail innovation have both partial and simultaneous significant effects on customer satisfaction, confirming their strategic role in strengthening retail competitiveness. Type of Paper: Identifies Research Article).